2020
DOI: 10.1177/1077546320912109
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic dynamics of cylindrical roller bearing supported by unbalanced rotor due to localized defects

Abstract: This article presents a nonlinear vibration signature study of high-speed defective cylindrical roller bearings under unbalance rotor conditions. Qualitative analysis is conducted considering a spall defect of a specific size on major elements such as outer race, inner race, and rollers. A spring-mass model with nonlinear stiffness and damping is formulated to study the dynamic behavior of the rotor-bearing model. The set of nonlinear differential equations are solved using the fourth-order Runge–Kutta method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Wen et al 18 proposed a dynamic model with multiple DOFs and revealed the effects of outer raceway defects with different sizes and position angles on the dynamic behaviors of the bearing. Patra et al 19 considered a spall defect of a specific size on the outer race, the inner race, and rollers, respectively, in the bearing model to predict the characteristics of the discrete spectra and analyze the stability of the system. Patil et al 20 considered the cage slip in the proposed dynamic model for bearing with inner raceway or outer raceway defects.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al 18 proposed a dynamic model with multiple DOFs and revealed the effects of outer raceway defects with different sizes and position angles on the dynamic behaviors of the bearing. Patra et al 19 considered a spall defect of a specific size on the outer race, the inner race, and rollers, respectively, in the bearing model to predict the characteristics of the discrete spectra and analyze the stability of the system. Patil et al 20 considered the cage slip in the proposed dynamic model for bearing with inner raceway or outer raceway defects.…”
Section: Introductionmentioning
confidence: 99%
“…Various defects like cracks, pits and spalls, dents, scratches, bump flanking and fault size prediction are part of localized defects, while surface roughness, waviness, and misaligned races and offsized rolling element comes under distributed defects. 10,11,14,[16][17][18][19][20] Faulty design, improper installation, lack of lubrication, and heavy fatigue loading are responsible for the generation of localized defects, while the distributed defects are caused because of faulty design, manufacturing errors. 20 There is a great influence on vibration response due to the occurrence of faults in different parts of bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Rotating machines are widely used in turbomachinery, compressors, generators, and aero-engines etc. [1][2][3] In aero-engines, in order to obtain a higher thrust-toweight ratio, a dual-rotor system in which the lowpressure (LP) and high-pressure (HP) rotors coupled with inter-shaft bearing is widely adopted, as presented in Figure 1. In contrast to the single-rotor systems, dual-systems may introduce coupling vibrations and contain multiple frequency inputs.…”
Section: Introductionmentioning
confidence: 99%